Back Cover: Plasma Process. Polym. 5∕2014. Issue 5 (May 2014) - Drabik, Martin; Kousal, Jaroslav; Celma, Coralie; Rupper, Patrick; Biederman, Hynek; Hegemann, Dirk
<x xml:space="preserve">Abstract</x> Back Cover: Acetone and carbon dioxide are used within a symmetric RF plasma discharge to deposit oxygenfunctional plasma polymer films that are exceptionally stable under aging conditions. Further details can be found in the article by Dirk Hegemann et. al. on page 496. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>